Oxidation of carbon nanotubes using for Cu(II) adsorption from aqueous solution - Quyen, Nguyen Duc Vu; Tuyen, Tran Ngoc; Khieu, Dinh Quang; Tin, Dang Xuan; Diem, Bui Thi Hoang; Tinh, Nguyen Thi My; Lan, Pham Thi Ngoc (Hue University Journal of Science: Natural Science, 2019)
Carbon nanotubes (CNTs) synthesized by chemical vapour deposition without using hydrogen were oxidized with 0.1 M potassium permanganate at 40oC for 2 hours and exhibited high CuII adsorption capacity from aqueous solution. X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), scanning electron microscope (SEM), transmission electron microscope (TEM) and nitrogen adsorption/desorption isotherms were used to characterize the oxidized CNTs. After oxidizing, the obtained CNTs were used to remove CuII from aqueous solution. With CuII initial concentration of 20 mg.L-1, at pH of 4 and adsorbent dosage of 0.2 g.L-1, the oxidized CNTs exhibited high CuII adsorption ability with maximum adsorption capacity of 174.4 mg.g-1.